Increasing advance directive completion within the 4R oncology model in patients with breast cancer prior to surgery in a racially diverse patient population. Issue 28 (1st October 2022) - Ossowski, Stephanie; Lyon, Liisa; Linehan, Elizabeth Shurell; Gordon, Nancy P.; Egorova, Olga; Mark, Becky; Beringer, Kimberly; Abbe, Thea; Shirazi, Aida; Weldon, Christine B.; Trosman, Julia R.; Ravelo, Arliene; et al.
Abstract : 54 Background: Advance directives (ADs) are an important part of life care planning in patients with cancer. There is a lack of effective interventions to increase AD rates in breast cancer patients prior to surgery. In this quality improvement project, we implemented an intervention for breast cancer patients receiving care in an integrated healthcare delivery system. 4R (Right Info / Right Care / Right Patient / Right Time) is a novel care planning and delivery model that enables the patient and oncology care team to manage complex time-sensitive care using a multi-modality 4R Care Sequence plan, coupled with follow-up workflows. Methods: We studied two groups of patients with newly diagnosed non-metastatic breast cancer who attended a multidisciplinary clinic and underwent definitive surgery at one facility. The Usual Care (UC) cohort received care from 10/1/19 to 9/30/20. The 4R Intervention (4R) cohort received care from 10/1/20 to 9/30/21 using a 4R Care Sequence plan that included AD completion prior to surgery; those without an AD were referred for follow-up to a health educator to discuss AD completion. Bivariate analyses were used to compare the UC and 4R cohorts on demographics, NCCN thermometer distress scores, and AD completion rates. Results: Characteristics of age, gender, race/ethnicity, needing interpreter, Elixhauser Comorbidity Index, NCCN distress scores > 4, surgery type, grade, ER/PR/HER-2 status were similar in the UC (N = 140) and 4R cohorts (N = 141). AD completion prior to surgery was significantly higher for the 4R vs. UC cohort, both overall (15% vs 74%, p <.01), and for White, Black, and Asian/PI subgroups (Table). The Hispanic subgroups were too small to compare AD completion. AD completion did not significantly differ by higher vs. lower distress scores. Conclusions: Implementation of a 4R Care Sequence plan coupled with health educator follow-up can significantly increase rates of time-sensitive AD completion, regardless of patient distress score and patient race/ethnicity. Use of an effective standardized care delivery model like 4R can promote equitable care.Number of patients with AD completed prior to surgery. Usual Care N = 140 Intervention N = 141 P value* All 21 (15%) 104 (73.8%) <.01 White 9 (16%) 45 (76%) <.01 Asian/PI 8 (17%) 41 (80%) <.01 Black 1 (17%) 11 (79%) .019 Hispanic 1(5%) 3 (27%) ns Other 2 (20%) 4 (67%) ns ns – not statistically significant *Fisher's exact 2-tailed test